Cost Optimization of Preventive Maintenance Using an Integer Linear Programming Approach Based on RCA and Markov Chain - Rino Indriyanto; Maria Ulfah; Ratna Ekawati (International Journal of Artificial Intelligence Research, 2026)
In 2024, the canned slurry pump at PT. X experienced 38 failure events, resulting in a total downtime of 105 hours and maintenance costs of IDR 3,193,283,735 due to the absence of a preventive maintenance program. This study proposes an integrated preventive maintenance optimization framework combining Root Cause Analysis (RCA), Markov Chain modeling, and Integer Linear Programming (ILP). RCA identifies six dominant failure causes accounting for 89.5% of total failures, which are used to define machine condition states in the Markov Chain model for estimating expected maintenance costs and predicting system behavior. The proposed maintenance policy (P?) reduces the average expected maintenance cost from IDR 333,486,618 to IDR 187,820,157, corresponding to a reduction of 43.68%. This value yields the most economical annual expected maintenance cost of IDR 1,798,000,000 and is subsequently applied as a cost constraint in the ILP model. The optimization results show that preventive maintenance for 10 pump units in 2025 can be implemented at a total cost of IDR 1,701,000,000 while generating an estimated profit of IDR 1,520,000,000. The results demonstrate that the proposed integrated approach enables effective and cost-efficient preventive maintenance decision-making, supported by the formulation of standardized working instructions in accordance with company standards.